Modern Methods and Criteria for Assessing theScientific-Pedagogical Activities of Master'sStudents - Khaydarova Makhliyo Khabibullayevna (Euro Asian Journal Publishing, 2025)
The article is devoted to modern methods and criteria for assessing the scientific-pedagogical activities of master's students. It examines issues related to organizing scientific research activities for master's students in pedagogical fields, measuring motivational-value indicators, and utilizing bibliometric analyses and rating-point systems. Mechanisms for assessing competencies during pre-diploma and production practice—dividing them into critical, sufficient, and advanced levels—are analyzed, along with the portfolio method and the development of innovative approaches through scientific seminars. It is emphasized that modern assessment methods enable comprehensive measurement of students' scientific activities in terms of process dynamics and outcomes, enhance motivation, and improve the quality of pedagogical education
Keywords: Master's degree; scientific-pedagogical activity; assessment methods